2011
DOI: 10.1093/carcin/bgr251
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pancreatic cancer by neuropsychological stress responses: a novel target for intervention

Abstract: Pancreatic cancer has a poor prognosis and is associated with high levels of psychological stress that may adversely affect clinical outcomes. However, the potential influence of neuropsychological factors on pancreatic cancer has not been investigated to date. Using a mouse model of social stress, we have tested the hypothesis that psychological stress promotes the progression of pancreatic cancer xenografts via neurotransmitter-induced activation of multiple pathways and that the inhibitory neurotransmitter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 43 publications
6
81
0
1
Order By: Relevance
“…In the present study, ISO increased the expression level of VEGF-A in HemECs in a β-AR- and ERK-dependent manner. These findings are consistent with previous studies in which β-AR stimulation resulted in the over-expression of VEGF-A through the β-AR and ERK signaling cascade [25,31,57]. …”
Section: Discussionsupporting
confidence: 93%
“…In the present study, ISO increased the expression level of VEGF-A in HemECs in a β-AR- and ERK-dependent manner. These findings are consistent with previous studies in which β-AR stimulation resulted in the over-expression of VEGF-A through the β-AR and ERK signaling cascade [25,31,57]. …”
Section: Discussionsupporting
confidence: 93%
“…32 Similarly, increased noradrenaline, adrenaline, cortisol, VEGF and cAMP in a social stress mouse model promoted the progression of pancreatic cancer xenografts, whereas reduction of cAMP by the inhibitory neurotransmitter g-aminobutiric acid (GABA) prevented tumor progression. 33 Poor prognosis in some epithelial cancers also has been correlated to perineural invasion, a process by which tumor cells migrate and proliferate along the nerves. A retrospective blinded analysis of prostate adenocarcinoma specimens has correlated the density of sympathetic and parasympathetic nerve fibers with a poor clinical outcome.…”
Section: Autonomic Regulation Of Hematopoiesis and Cancermentioning
confidence: 99%
“…Gene-knockdown of Gα i -coupled GABA-B receptors (GABA-B-Rs) blocked these effects of GABA while transient overexpression of GABA-B-Rs enhanced these responses to GABA, identifying the Gα i -mediated inhibition of adenylate cyclase activation as the underlying mechanism [11]. In accord with these in vitro findings, the progression of PDAC xenografts in athymic nude mice was significantly inhibited in the absence and presence of chronic exposure to nicotine or social stress by treatment of the animals with GABA in the drinking water [12, 24]. GABA treatment also enhanced the responsiveness of PDAC xenografts to the cancer therapeutic agent celecoxib in the absence and presence of social stress [25].…”
Section: Introductionmentioning
confidence: 99%
“…[11]. Investigations with mouse xenografts from human PDAC cell lines additionally showed that chronic psychological stress and the resulting systemic increase in stress neurotransmitters significantly promoted tumor growth via the cAMP-driven activation of multiple signaling pathways downstream of beta-adrenergic receptors while suppressing GABA [12]. Moreover, a recent study in an orthotopic mouse model of PDAC provided evidence that stress neurotransmitters released from sympathetic nerves in the pancreatic environment in response to chronic stress increased tumor progression and that this response was inhibited by beta-blocker treatment [13].…”
Section: Introductionmentioning
confidence: 99%